Media Flash Card dalam Pembelajaran Keterampilan Berbicara di Madrasah Tsanawiyah - Syifa, Nurusy; Maswani, Maswani; Rahmawati, Siti Urianah (Department of Arabic Education - Faculty of Educational Sciences, 2022)
The researcher chose this topic because teaching speaking skill has problems, including: Students' lack of inclination to speak Arabic, not using the medium to teach speaking skill, the lack of students' interaction in teaching Arabic and the lack of students' motivation to speak. The purposes of this research are: (1) To know use of flash card media in speaking skil learning at Al-Ihsan Islamic middle school Jakarta, (2) to know is the student ability of using the flash card media in speaking skil learning at Al-Ihsan Islamic middle school Jakarta (3) To know how far is the effectiveness of using the flash card media in speaking skil learning at Al-Ihsan Islamic middle school Jakarta. This research is a quantitative research, with an experimental method that uses the type of one group pretest posttest design. While the method of data collections were using observation, interviews, oral test and documentation. After the researcher carried out the pre-test and post-test activities orally, the researcher obtained the average result, the pre-test was 63.71 and the post-test average result was 70.57 then analyzed it with the T-test and got the t-table results. (0.975) which is 1.99 while the t-count is 16.41 which is greater than the result of the t-table. And shows the comparison value that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The researcher knows that the application of flashcard media has proven its effect on speaking skills.